Specifying the dimensions of care that matter to people with long-term conditions (LTCs) and improving our understanding of patient-centred care (PCC) - Hadi, M (2014)
Background The term patient-centred care (PCC) is commonly used in the academic literature and UK health policy. However, this concept is ill defined and little is known about its applicability to the management of people with long-term conditions (LTCs). Several methodologies were used to explore the meaning of PCC, identify key experiences that matter to people with LTCs and consider the implications of these findings for the measurement of patient reported experiences of health care. Method Four stages of research were conducted for this thesis. First, a conceptual synthesis of existing PCC and patient experience frameworks to produce an overarching framework of PCC. Second, secondary qualitative analysis of patient interviews to identify key experiences of PCC that matter to people with LTCs. Third, development of a PCC questionnaire for people with LTCs, based on findings from the conceptual synthesis and secondary analysis. Fourth, further exploration of the questionnaire through cognitive debriefing interviews with people with LTCs and health professionals. Results The overarching framework of PCC consisted of 8 domains; access, availability and choice, information, communication and education, relationship with health professionals, involvement in care, respect and dignity, responsiveness to individual needs and preferences, consistency, continuity and co-ordination, and effectiveness of treatment and care. Findings from secondary analysis suggested that many of the domains from the framework were also important in care for people with LTCs, but that some aspects of care held an additional meaning. The themes identified in the secondary analysis were used to generate items for a generic PCC experience questionnaire for people with LTCs. The final questionnaire, ‘Your Experiences of Care in Long-Term Conditions’ consisted of 47 questions across three sections. Feedback from the debriefing interviews suggested that the questionnaire had asked important questions about care for people with LTCs and that it was relevant to people with a range of different LTCs. Conclusion Development of an overarching framework of PCC demonstrated some conceptual problems in understanding and evaluating the notion of PCC. Findings from this thesis suggest that an overarching questionnaire of experiences of PCC is feasible and acceptable to people with a range of different LTCs. Future research needs examine standard features of the newly developed PCC experience questionnaire for people with LTCs and consider the potential use and contribution of data in enhancing care for people with LTCs.